2013
DOI: 10.1021/la401707u
|View full text |Cite
|
Sign up to set email alerts
|

Facile One-Step Synthesis and Transformation of Cu(I)-Doped Zinc Sulfide Nanocrystals to Cu1.94S–ZnS Heterostructured Nanocrystals

Abstract: A facile one-pot heating process without any injection has been developed to synthesize different Cu-Zn-S-based nanocrystals. The composition of the products evolves from Cu(I)-doped ZnS (ZnS:Cu(I)) nanocrystals into heterostructured nanocrystals consisting of monoclinic Cu1.94S and wurtzite ZnS just by controlling the molar ratios of zinc acetylacetonate (Zn(acac)2) to copper acetylacetonate (Cu(acac)2) in the mixture of n-dodecanethiol (DDT) and 1-octadecene (ODE). Accompanying the composition transformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 51 publications
1
38
0
Order By: Relevance
“…According to these authors, approaching room temperature no ternary compounds are found, while only binary mixtures between ZnS and the numerous phases of the Cu-S and Cu-Zn binary diagrams exist. In spite of this lack of miscibility between the three constituents [27][28], proposed the mixtures of binary terms as novel materials for optoelectronic devices, especially if in nanometric dimension. Accordingly, the aims of this study include the verification of the possible occurrence of a ternary film with E-ALD.…”
Section: Introductionmentioning
confidence: 99%
“…According to these authors, approaching room temperature no ternary compounds are found, while only binary mixtures between ZnS and the numerous phases of the Cu-S and Cu-Zn binary diagrams exist. In spite of this lack of miscibility between the three constituents [27][28], proposed the mixtures of binary terms as novel materials for optoelectronic devices, especially if in nanometric dimension. Accordingly, the aims of this study include the verification of the possible occurrence of a ternary film with E-ALD.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, copper sulphide-cadmium sulphide hetero-nanostructures, which have a type II band alignment, facilitating the separation of light induced charge carriers, are interesting candidates for nanostructured solar cells [50]. Similar properties are also expected for PbS or the less toxic ZnS, attached to copper sulphide nanoparticles [21,24,[51][52][53][54]. The presence of ZnS or MnS can strongly influence the position of the plasmon band of copper sulphide particles.…”
Section: Copper Sulphide-based Hybrid Nanostructuresmentioning
confidence: 88%
“…As far as we know, there are few attempts to synthesize mixed Cu-Zn sulphide compounds [27][28][29][30][31][32][33][34] . Uhuegbu et al claimed to have synthesized Cu-Zn-S compounds through a one-pot synthesis with metal chlorides and thiourea in solution, assisted by opportune complexing agents 27 .…”
Section: Phases Occurring In the Cu-zn-s Compositional Fieldmentioning
confidence: 99%